The impact of the relationship between the state, state institutions and tax payers on willingness to pay tax - Dobos, Piroska; Takács-György, Katalin (Serbian Journal of Management, 2020)
There are several economic models in the literature that seek to correlate between human behaviour patterns, attitudes, tax evasion and its risk, also their institutional background. The values, the societal norms and attitudes differ from country to country, and these differences have a measurable effect on economic manners. Unethical business behaviour and the reasons of hidden economy are widely examined by more kinds of research methods. According to the results of many studies, we can assume that the trust in government, the stability of the tax system, and treating taxpayers as partners and with respect have positive effect on willingness to pay tax. Apart from this, direct political participation of the citizens and their involvement in political decisions and democracy have significant positive effect on tax morals as well. The aim of present study is to support these statements based on a questionnaire survey among the competent managers of small and medium-sized enterprises in Hungary and with the help of in-depth interviews - from an economic psychological perspective - with some interviewees present in several countries as taxpayers.